Cultural Values in the Novel Gadis Pantai by Pramoedya Ananta Toer: A Literary Anthropology Study - Muyassaroh; Dita Amalia Putri Agustina; Zahrotun Mas Udah (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The purpose of this research is to describe the cultural values ​​in the novel Gadis Pantai by Pramoedya Ananta Toer. This research uses qualitative methods through literature study activities. The data source comes from the novel Gadis Pantai by Pramoedya Ananta Toer. The data collection technique used is reading and note-taking techniques. The results obtained in this study are (1) the language used in the novel Gadis Pantai by Pramoedya Ananta Toer; (2) the knowledge system in the novel Gadis Pantai by Pramoedya Ananta Toer; (3) the social system in the novel Gadis Pantai by Pramoedya Ananta Toer; (4) living equipment and technology systems in the novel Gadis Pantai by Pramoedya Ananta Toer; (5) the livelihood system in the novel Gadis Pantai by Pramoedya Ananta Toer; (6) the religious system in the novel Gadis Pantai by Pramoedya Ananta Toer; and (7) art in the novel Gadis Pantai by Pramoedya Ananta Toer.